EKSPERIMENTASI MODEL PEMBELAJARAN THINK PAIRSHARE MODIFIKASI PENEMUAN TERBIMBING BERBANTUAN MICROSOFT POWER POINT PADA PEMBELAJARAN MATEMATIKA DITINJAU DARI KEDISIPLINAN BELAJAR - ANAS, MIFTACHUL; Kusmayadi, Tri Atmojo; Suyono, Suyono (Jurnal Pembelajaran Matematika, 2013)
Abstract: The objective of this research was to investigate: (1) which of the Modified TPS learning model, the TPS learning model, and the conventional learning model results in a better mathematics learning achievement; (2) which of the students with high, mediun, and low learning disciplines have a better mathematics learning achievement; and (3) which of the Modified TPS, TPS and conventional learning models result in a better learning achievement for each level of learning discipline of the students; and (4) which of the high, medium, and learning disciplines of the students result in a better learning achievement for each learning models.This research used the quasi-experimental method. The population of this research was all students of the junior secondary schools in Ngawi regency in the academic year of 2012/2013. The samples of this research consisted of 284 students who were divided into three experiment groups. The three groups consisted of group 1, group 2, and group 3. Both of group 1 and group 2 consisted of 190 students whereas group 3 consisted of 94 students. The data of this research were gathered from test of learning achievement in Mathematics, questionnaire, and documentation. The data were then analyzed by using umbalanced Two-way Analysis of Variance.The result of the research are as follows: (1) the learning model of Modified TPS is better than that of the TPS and conventional learning models while the learning model of TPS is better than the conventional learning model; (2) the students with high learning discipline have a better learning achievement than those with medium and low learning discipline while the students with medium learning discipline is better than the low learning discipline; (3) in high and medium learning discipline of the students,the learning achievement achieved through the learning model of Modified TPS is better than that achieved through the TPS and conventional learning models while the learning achievement achieved through the TPS learning model is better than that achieved through the conventional learning model. However, in the low learning discipline of the students,the learning achievement achieved through the learning model of Modified TPS is better than that achieved through the TPS,andthe Modified TPS learning model is as good as the conventional learning model and the TPS learning model is as good as the conventional learning model; and (4) in Modified TPS and TPS of the learning models, the high learning discipline of the students results in a better learning achievement than the medium and low learning disciplines while the medium learning discipline results in a better learning achievement than the low learning discipline. However, in the conventional learning model the high learning discipline of the students results in a better learning achievement than the medium learning model, andthe medium learning discipline of the students are giving the same mathematics learning achievement with the low learning discipline.Keyword : Modified TPS learning model, TPS learning model, conventional learning model, learning discipline and learning achievement.